Stakeholder Collaboration and Tourism Value Creation: A Bibliometric Analysis of Sustainable Tourism Research - Heri Nurranto (Yayasan Ilomata, 2026)
Stakeholders play a crucial role in generating value within the tourism sector, as destination attractiveness alone is insufficient to ensure sustainable competitiveness. Tourists’ value expectations increasingly determine the success of tourism destinations. This study aims to map and analyze scientific publications related to stakeholders and tourism value using a bibliometric approach. Data were retrieved from the Dimensions database using the search string (“stakeholder” AND “value tourism”) applied to title, abstract, and keyword fields. After data cleaning and screening, a total of 895 peer-reviewed journal articles published between 2015 and 2024 were included. Bibliometric analysis was conducted using VOSviewer, focusing on publication trends, co-authorship networks, citation structures, total link strength, and keyword co-occurrence patterns. The results indicate a consistent growth in research related to stakeholders in tourism over the past decade, highlighting increasing academic attention to value creation and sustainable tourism development. The keyword co-occurrence analysis indicates that stakeholder-related value tourism frequently appears in peripheral cluster positions and exhibits lower total link strength compared to dominant themes such as tourist satisfaction and destination performance. This study contributes to the tourism literature by identifying emerging themes, research gaps, and potential directions for future studies, particularly in stakeholder collaboration and value co-creation. Practically, the findings provide insights for destination management organizations and policymakers to strengthen stakeholder involvement in developing sustainable tourism and enhancing destination brand equity.